A Chinese Word by Jacques Derrida. Issue 2 (November 2021) - Castaño, Héctor G.
Abstract : Some scholars claim that in Derrida's Of Grammatology the author presents China and its script as essentially and radically Other when compared to the West. In this paper, I argue that Derrida's discussion of Leibniz, his critique of the notions of 'phonetic writing' and 'ideograph', and the distinction he makes between 'logocentrism' and 'phonocentrism', enables him to deconstruct an essentialist conception of China or Chinese writing. However, far from conceiving China in a relativist or ethnocentric manner, Derrida also pays attention to the historicity of the encounter between European philosophy and China. In order to underline the transcultural potential of deconstruction, I discuss the concept of 'crypt' in light of the Chinese translation of the word ' différance '. This allows me to reinterpret what I claim to be Derrida's problematic reference to Chinese writing as 'outside of all logocentrism' from the point of view of his philosophy of translation. 1